List of Spanish seamen in ports in the United Kingdom, as shewn by latest receipts
C01-0039-001 25 September, 1940. LIST OF SPANISH SEAMEN IN PORTS IN THE UNITED KINGDOM, AS SHEWN BY LATEST RECEIPTS. BARRY Feliciano BIDEA BELFAST 1 Bonifacio ARANGUENA Acha Liverpool (wife, 2 chldrn). 2 Bonifacio AZCUNE Mendive 3 Ramon de la CRUZ Argote (wife, 2 chldrn). 4 Luis DIAZ de Lasaga 5 Bonifacio ESTEBAN Garcia 6 Manuel FERNANDEZ Fernandez 7 Juan Jose GOMEZ aPraiz 8 Jose Maria GONDRA y Ozamiz 9 Andres GUENECHEA Uranga (wife) 10 Julian de IRIBAR e Ydoyaga (wife) 11 Jose RAMA Riomayor BIRKENHEAD 1 Leon ARRAIBI Estancona 48 MR 2 Deogracias BURGANA Guezuriaga 90 PL 3 Jose FERNANDEZ Murias 37 PL 4 Jesus LAGAREJOS Larrabide 5 Jose B. MARCAIDA (wife) 48 Mallery Rd B/d 6 Pablo YGARTUA Sustacha 7 Lamberto BASARRATE 10 June (wife) 8 Manuel FREIRE (wife, child) 9 Ignacio IBARZABAL 10 Vicente REY 1 Aug. BRISTOL 1 Miguel MORAL Aguirre 2 Felix R. PACHECO CARDIFF 1 Alberto AGUIRRE 719 Bute St. 2 Santos BASAURI Egusquiaguirre 16 Louisa St. (wife) 3 Juan LARRASQUITU Torre 211 Corporation Rd (wife) 4 Antonio LARRASQUITU Mugica 7, Abercynon St. 5 Jose ORPI Palan 8 Louisa St. (wife, child) 6 Eduardo del PRADO Rojas 35, Louisa St. HULL 1 Fortunato LUNO Bilbao (wife) 2 Juan UGARTE y Ugarte (wife) LONDON Marcelo ARENAZA NEWCASTLE -on- TYNE 1 Jose GUILLEN Olveira 2 Delfin PASCUAL 3 Ignacio ARANO 4 Ramon GUERRERO 5 J. ARREGUI 6 Ramon SOLIS 7 Francisco CALO PLYMOUTH 1 Pedro DOMINGUEZ 2 Jose Luis URRUTIA SUNDERLAND Captain and daughter. WEST HARTLEPOOL 1 Carmelo ABADIA 2 Juan FEDALGO 3 Juan FERNANDEZ 4 Primitivo GONZALEZ 5 Vicente FERNANDEZ 6 Aureliano LARANGOGOITIA 7 Victor LARREA [shorthand notes] 292C/946/1/39